A Comprehensive Review of the Usefulness of Prebiotics, Probiotics, and Postbiotics in the Diagnosis and Treatment of Small Intestine Bacterial Overgrowth - Adrian Martyniak; Magdalena Wójcicka; Iwona Rogatko; Tomasz Piskorz; Przemysław J. Tomasik (Microorganisms)
Small intestinal bacterial overgrowth (SIBO) is a disorder characterized by the excessive growth of bacteria in the small intestine. Bacterial overgrowth disrupts the bacterial balance and can lead to abdominal pain, weight loss, and gastrointestinal symptoms, including bloating, diarrhea, and malabsorption. SIBO is widespread in the population. There are two main methods for diagnosing SIBO: breath tests and bacterial culture. The most commonly used method is a breath test, which enables the division of SIBO into the following three types: hydrogen-dominant (H-SIBO), methane-dominant (CH4-SIBO), and hydrogen/methane-dominant (H/CH4-SIBO). This comprehensive review aims to present the current knowledge on the use of prebiotics, probiotics, and postbiotics in the context of SIBO. For this purpose, medical databases such as MEDLINE (PubMed) and Scopus were analyzed using specific keywords and their combinations. This review is based on research studies no older than 10 years old and those using only human models. In summary, clinical studies have shown that the efficacy of SIBO therapy can be increased by combining antibiotics with probiotics, especially in vulnerable patients such as children and pregnant women. The further development of diagnostic methods, such as point of care testing (POCT) and portable devices, and a better understanding of the mechanisms of biotics action are needed to treat SIBO more effectively and improve the quality of life of patients.